Kampanye Isi Piringku untuk Kejadian Stunting pada Balita - Gita Adelia; Dini Maulinda; Sri Widya Ningsih; Fitri Dyna; Angga Arfina; Eka Malfasari (HEALTH CARE : JURNAL KESEHATAN, 2022)
Introduction: Stunting is a chronic malnutrition problem that causes growth disorders, namely the child's height is lower or shorter (short) than the standard age. One of the current government focuses is stunting prevention by promoting the “Fill My Plate” Campaign. Objective: to determine the relationship between mother's knowledge about the "Fill My Plate" Campaign with the incidence of stunting in toddlers in the working area of ​​the Sidomulyo Inpatient Health Center Pekanbaru. Method: This study is quantitative with a correlation design using a cross-sectional approach. Data collection in this study was carried out using a consecutive sampling technique in March-August 2021 on 70 mothers and toddlers. The measuring instrument used is a knowledge questionnaire and a microtaise which is then analyzed using the chi square test (p-value <0.05). Results: Of the 18 respondents who had toddlers with stunting problems, 83.3% had high knowledge. The results of the chi-square test obtained p value 0.71 (p value > 0.05) meaning Ha is rejected so it can be concluded that there is no relationship between mother's knowledge about the "Fill My Plate" campaign with the incidence of stunting in toddlers in the working area of ​​the Sidomulyo Inpatient Health Center Pekanbaru. Mothers with low knowledge are 1 times more likely to have children with stunting. Recommendations It is hoped that further researchers can analyze the application of the contents of my plate to the incidence of stunting or other related matters that can improve stunting prevention in children in Indonesia